Assessing Postgraduate Surgical Training Needs at Two Private Tertiary Care Hospitals: A Descriptive Study : Assessing Surgical Training Needs in Private Hospitals - Nadia Shahid; Rabia Aftab; Aurangzeb Shaikh; Aun Ali; Muhammed Ahmed (Journal of University College of Medicine and Dentistry, 2025)
Objective: To assess the perceived learning needs and challenges faced by postgraduate surgical residents at two private tertiary care hospitals, with the aim of identifying areas for improvement in the structure and delivery of surgical training programs. Method: A cross-sectional, descriptive observational study was conducted from May 2023 to January 2024 at two private medical colleges offering structured residency programs in Surgery and Allied specialties. Postgraduate residents from years one to four were recruited through purposive sampling after obtaining ethical approval and informed consent. A 23-item questionnaire, developed from literature and pilot-tested for clarity, was administered via Google Forms to 57 residents. Responses were collected using a 5-point Likert scale and subsequently grouped into three categories: disagree (1–2), neutral (3), and agree (4–5). Participants were stratified into junior (years 1–2) and senior (years 3–4) groups. Data were analyzed using SPSS version 24. Chi-square or Fisher’s exact tests were applied, with a p-value of <0.05 considered statistically significant. Results: Overall, 87% of respondents reported receiving specific learning objectives at the start of each rotation—80% of juniors and 93.3% of seniors. Although 65.5% felt they achieved the expected learning outcomes, only 29% perceived the training to be well-structured. A majority (76.3%) expressed dissatisfaction with opportunities to serve as primary surgeons. Feedback was limited; only 30% reported receiving supervisor feedback. While over 60% of residents were familiar with the curriculum and had access to educational resources, only 20% received a formal orientation. Confidence in achieving learning goals was reported by 61.8%, with overall training satisfaction noted in 60% of juniors and 56.7% of seniors. Conclusion: The study highlights key gaps in surgical training, including inadequate operative exposure, limited feedback mechanisms, and the need for structured evaluation and orientation practices.